A study measuring the effects of customer empowerment in co-creation - Gregory, Alex (2016)
This study aimed to examine to what extent different types of customer empowerment effects consumers attitudes towards products and how this influences their behavioural intentions towards the product. Behavioural intentions under investigation are purchase intentions, word of mouth, and willingness to pay. As a major source of competitive advantage, co-creation is becoming increasingly important for firms to implement into their strategic planning and product innovation, especially as a form of differentiation as product categories become more and more commoditized. Previous studies have focused mostly on co-creation from a service perspective, for instance its role in financial institutions, whereas studies on its role in product innovation is a relatively new and untouched field of study. This study not only focuses on the effects of customer empowerment in co-creation but also considers the influence of product complexity and how high and low complexity products may encourage consumers to evaluate differently.